Broken benefits : what's gone wrong with welfare reform - Royston, Sam (Policy Press, 2017)
Britain is going through the most radical upheaval of the benefits system since its foundations were laid at the end of the 1940s. In Broken Benefits, Sam Royston argues that social security isn't working, and without a change in direction, it will be even less fair in the future. Drawing on original research and high-profile debates, this much-needed book provides an introductory guide to social security, correcting misunderstandings and exposing poorly understood problems. It reveals how some workers pay to take on additional hours; that those who pay national insurance contributions may g.